IMPROVING SPIRITUAL INTELLIGENCE THROUGH ROLE PLAY - Wahyuni Nadar (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2018)
Abstract:. In general, the purpose of this study is to obtain data about the spiritual intelligence of children aged 5-6 years in the center of al Islam KB TK Bunga Bangsa Islamic School through role play. This research was conducted at KB TK Bunga Bangsa Islamic School Bekasi which is located on Jl. Kh. Agus Salim Number 206, Kelurahan Margahayu, District of East Bekasi, Kota Bekasi, West Java Province. Specifically this research will see how big role play can improve every aspect that exist in spiritual intelligence for children aged 5-6 years at KB TK Bunga Bangsa Islamic School Bekasi. This research was conducted in second semester of academic year 2016/2017. This action study was conducted using a cycle model from Stephen Kemmis and Mc Taggart. Action research is carried out through planning, implementation, observation and reflection. This research was conducted in two cycles and started with pre-research activities. The average praintervensi result is 57%, in cycle 1 the result is 65,5% and cycle 2 reaches 80% on average. From the data there is a significant increase in each cycle. Improvement is seen in every aspect that depicts children's spiritual intelligence such as self-awareness, spontaneity, internally motivated, seeing life from vision and based on fundamental, holistic values, seeing system and universality, compassion (sense of community, sense of following the flow of life) diversity, independent, firm against the majority, fundamentally questioning, rearranging in the big picture, and steadfast in difficulty.Thus, the learning process through the role play to improve spiritual intelligence is said to have been achieved because most of the indicators in the competence of the ability of spiritual intelligence has increased. The implication of this research is that role playing can be one strategy to improve spiritual intelligence.Keyword: Spiritual Intelligence, role play, action research Abstrak: Secara umum tujuan penelitian ini yaitu untuk mendapatkan data data tentang kecerdasan spiritual anak usia 5-6 tahun di sentra al Islam KB TK Bunga Bangsa Islamic School melalui bermain peran. Penelitian ini dilakukan di KB TK Bunga Bangsa Islamic School Bekasi yang belokasi di Jl. Kh. Agus Salim Nomor 206, Kelurahan Margahayu, Kecamatan Bekasi Timur, Kota Bekasi, Propinsi Jawa Barat. Secara khusus penelitian ini akan melihat seberapa besar bermain peran dapat meningkatkan setiap aspek yang ada dalam kecerdasan spiritual untuk anak usia 5-6 tahun di KB TK Bunga Bangsa Islamic School Bekasi Penelitian ini dilakukan pada semester II tahun ajaran 2016/2017. Penelitian tindakan ini dilaksanakan dengan menggunakan model siklus dari Stephen Kemmis dan Mc Taggart. Penelitian tindakan dilaksanakan melalui tahap perencanaan, pelaksanaan, observasi dan refleksi. Penelitian ini dilaksanakan dalam dua siklus dan diawali dengan kegiatan pra penelitian. Hasil rata-rata praintervensi sebesar 57 %, pada siklus 1 hasil rata-rata 65,5 % dan siklus 2 mencapai rata-rata 80 %. Dari data tersebut terlihat adanya peningkatan yang signifikan di setiap siklus. Peningkatan terlihat disetiap aspek yang menggambarkan kecerdasan spiritual anak seperti kesadaran diri, spontanitas, termotivasi secara internal, melihat kehidupan dari visi dan berdasrkan nilai-nilai fundamental, holistik, melihat sistem dan universalitas, kasih sayang (rasa berkomunitas, rasa mengikuti aliran kehidupan), menghargai keragaman, mandiri, teguh melawan mayoritas, mempertanyakan secara mendasar, menata kembali dalam gambaran besar, dan teguh dalam kesulitan. Dengan demikian, proses pembelajaran dengan melalui bermain peran untuk meningkatkan kecerdasan spiritual dikatakan sudah tercapai karena sebagaian besar indikator dalam kompetensi kemampuan kecerdasan spiritual telah meningkat. Implikasi hasil penelitian ini adalah bahwa bermian peran dapat dijadikan salah satu strategi  untuk meningkatkan kecerdasan spiritual.Kata Kunci: Kecerdasan spiritual, bermain peran, penelitian tindakan